MELK is an oncogenic kinase essential for early hepatocellular carcinoma recurrence. Issue 1 (1st December 2016) - Xia, Hongping; Kong, Shik Nie; Chen, Jianxiang; Shi, Ming; Sekar, Karthik; Seshachalam, Veerabrahma Pratap; Rajasekaran, Muthukumar; Goh, Brian Kim Poh; Ooi, London Lucien; Hui, Kam M.
Abstract: Hepatocellular carcinoma (HCC) is the second leading cause of cancer-related deaths worldwide. Many kinases have been found to be intimately involved in oncogenesis and the deregulation of kinase function has emerged as a major mechanism by which cancer cells evade normal physiological constraints on growth and survival. Previously, we have performed gene expression profile analysis on HCC samples and have identified a host of kinases that are remarkably overexpressed in HCC. Among these, the Maternal Embryonic Leucine Zipper Kinase (MELK) is highly overexpressed in HCC and its overexpression strongly correlates with early recurrence and poor patients' survival. Silencing MELK inhibited cell growth, invasion, stemness and tumorigenicity of HCC cells by inducing apoptosis and mitosis. We further showed that the overexpression of MELK in HCC samples strongly correlated with the cell cycle- and mitosis-related genes which are directly regulated as part of the forkhead transcription factor FoxM1-related cell division program. Together, our data establish MELK as an oncogenic kinase involved in the pathogenesis and recurrence of HCC and could provide a promising molecular target to develop therapeutic strategies for patients with advanced HCC. Highlights: MELK is overexpressed in HCC and correlates with early recurrence and survival. Silencing MELK inhibits growth, invasion, stemness and tumorigenicity of HCC cells. MELK regulates cell cycle progression and mitosis-related genes through targeting FOXM1.